Analisis Kausalitas Pertumbuhan Ekonomi, Indeks Pembangunan Manusia Dan Belanja Modal Di Provinsi.Jambi - Yolanda Sari; Etik Winarni; Muhammad Amali (Ekonomis: Journal of Economics and Business, 2021)
This research aims toaanalyze the causal relationshipbbetween several variables including economiccgrowth using the value of PDRB at constant prices, the variable humanndevelopment index (HDI) and capitaleexpenditures in Jambi Province during 2010-2020 period. The data used in this research is secondary data with a database obtained from BPS Jambi Province and Regional Financial Statistics Jambi Province. The method used in this research is the Granger causality analysis method, which was previously tested using unit roots and cointegration methods to see the long-termrrelationship betweenrresearch variables. The results showed that there was a long-term relationship between the research variables. Economic growth has a one-way causal relationship with HDI. Economic growth increases the supply of resources needed for human development which in turn will encourage better human development. The capital expenditure variable has a one-way causal relationship with the economic growth variables. The allocation of capital for the implementation of various community economic activities and become an economic stimulus in Jambi Province.